New solitary wave solutions and conservation laws to the Kudryashov-Sinelshchikov equation - İnç, Mustafa; Aliyu, Aliyu Isa; Yusuf, Abdullahi; Baleanu, Dumitru (Elsevier Gmbh, Urban & Fischer Verlag, 2017)
In this manuscript, we utilized the algorithm of Riccati Bernoulli sub-ODE method to find new soliton solutions to the Kudryashov Sinelshchikov equation (KSE). Some new type of traveling wave solutions are acquired, which includes the kink-type, singular-type and exponential function solutions which have not been obtained in previous time using this technique. The obtained solutions appear with all necessary constraint conditions that are necessary for them to exist. Using the general conservation laws (Cls) theorem introduced by Ibragimov, the Cls for the underlying equation are investigated. (C) 2017 Elsevier GmbH. All rights reserved.
Keywords: Lie symmetry; Soliton solutions; Conservation laws